(untitled) (Journal of Foreign Language Studies, 2024)
This article introduces and compares the Bloom’s Taxonomy and the Bloom’s revised Taxonomy. On the basis of the identified advantages of Bloom’s revised Taxonomy, focus is made on explaining and analysing the process of applying this version to formulating competence-oriented learning objectives and carrying out assessment activities of the Introduction to Linguistics course at the Faculty of Foreign Languages, Academy of Finance.